Hyperimmunoglobulinemia D syndrome with recurrent perianal abscess successfully treated with canakinumab. Issue 3 (August 2019) - Miray Kisla Ekinci, Rabia; Balcı, Sibel; Bisgin, Atil; Tumgor, Gokhan; Dogruel, Dilek; Yilmaz, Mustafa
Hyperimmunoglobulinaemia D syndrome is an autoinflammatory disease usually representing recurrent episodes of fever, arthralgia/arthritis, cervical lymphadenopathy, vomiting, diarrhoea, abdominal pain and skin rashes lasting 3–7 days every 4–8 weeks since their infancy. Recent reports suggested a link between perianal fistulae/abscess and severe colitis with hyperimmunoglobulinaemia D syndrome resembling an inflammatory bowel disease phenotype. Herein, we report an 18-month-old patient with recurrent attacks of fever and pharyngitis lasting 2–3 days every 10–15 days since the first two weeks of life. Inflammatory attacks were accompanied by diarrhoea, oral aphthous ulcers, cervical lymphadenopathy, maculopapular rash, severe leukocytosis and perianal fistulae/abscess. After the initiation of canakinumab, the patient was clinically improved with complete healing of perianal fistulas/abscesses. In conclusion, hyperimmunoglobulinaemia D syndrome should be considered in differential diagnosis of inflammatory bowel disease and recurrent perianal abscess/fistula in a patient with inflammatory attacks.